2016
DOI: 10.1016/j.fertnstert.2015.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Novel fumarate hydratase mutation in a family with atypical uterine leiomyomas and hereditary leiomyomatosis and renal cell cancer

Abstract: Patients with HLRCC are at risk for developing renal cancer as well as losing their fertility via early hysterectomy. Physicians must be aware of this condition and refer at-risk individuals for genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Additionally, FH mutations in LMS have occasionally been reported 21, 22 . In those leiomyomas with FH gene mutations, some have characteristic histologic features, defined as SMT-FH 10, 11 (Table 4). These tumors are typically cellular with eosinophilic macronucleoli, perinucleolar halos, and eosinophilic cytoplasmic globules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, FH mutations in LMS have occasionally been reported 21, 22 . In those leiomyomas with FH gene mutations, some have characteristic histologic features, defined as SMT-FH 10, 11 (Table 4). These tumors are typically cellular with eosinophilic macronucleoli, perinucleolar halos, and eosinophilic cytoplasmic globules.…”
Section: Discussionmentioning
confidence: 99%
“…Further histologic analysis has revealed that some ULM with FH mutations have different nuclear and histologic features and can be referred to as smooth tumors with features of fumarate hydratase alteration (SMT-FH) 9, 10 . Historically, many sporadic SMT-FH were diagnosed as LM-BN due to the significant nuclear atypia 11, 12 . LM-BN also present with a wide range of histologic features 1, 3, 4 and in our set of tumors originally diagnosed as LM-BN, nearly half showed nuclear features similar to SMT-FH 9, 10 and we therefore defined them as type I LM-BN 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the mutation of FH gene in the NCCFH1 cell lines from a metastatic hereditary papillary renal cell carcinoma type 2 (PRCC2) results in glucose-dependent growth and impaired oxidative phosphorylation, which is consistent with the Warburg effect [ 9 ]. A clinic study shows that the mutation of FH gene results in the Reed syndrome, which is an autosomal dominant disorder characterized by cutaneous leiomyomas, uterine leiomyomas [ 15 ], and renal cell carcinoma [ 7 , 16 , 17 ], possibly representing genetic heritage lesions [ 18 ]. In addition, FH deficiency also could lead to metabolic disorders with severe encephalopathy, seizures and poor neurological outcome [ 10 ], suggesting an important role of FH in neurology as well.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal FH function/expression impairs mitochondrial function directly and has indirect effects on both glucose metabolism and oxidative phosphorylation by inappropriate activation of HIF1α and NRF2 [ 24 , 25 ]. Recently, there are reports showing that the mutation of FH may initiate renal cell carcinogenesis [ 7 , 9 , 18 , 26 29 ], implying tumor suppressor function of this gene. In our current study, we have histologically and immunohistochemically examined the kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 77% of histopathologic hysterectomy specimens demonstrate the presence of uterine leiomyomas 1 , 2 . Cytogenetic studies have shown that 40% to 50% of leiomyoma specimens exhibit chromosomal rearrangements and up to 70% of specimens display somatic mutations 1 , 3 . Despite the aforementioned genetic abnormalities, which may play a role in leiomyoma tumorigenesis, the only known genetic syndrome that leads to uterine leiomyomas is hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome.…”
mentioning
confidence: 99%